The 60- and 70-kDa heat-shock proteins and their correlation with cardiovascular risk factors in postmenopausal women with metabolic syndrome - Nahas, Eliana A. P. (Springer Netherlands, 2013)
We investigated the association between circulating levels of 60 and 70 kDa heat-shock proteins (HSP60 and 70) and cardiovascular risk factors in postmenopausal women with or without metabolic syndrome (MetS). This cross-sectional study included 311 Brazilian women (age ≥45 years with amenorrhea ≥12 months). Women showing three or more of the following diagnostic criteria were diagnosed with MetS: waist circumference (WC) ≥88 cm, blood pressure ≥130/85 mmHg, triglycerides ≥150 mg/dl, high-density lipoprotein (HDL) <50 mg/dl, and glucose ≥100 mg/dl. Clinical, anthropometric, and biochemical parameters were collected. HSP60, HSP70, antibodies to HSP60 and HSP70, and C-reactive protein (CRP) levels were measured in serum. Student's t test, Kruskal–Wallis test, chi-square test, and Pearson correlation were used for statistical analysis. Of the 311 women, 30.9 % (96/311) were diagnosed with MetS. These women were, on average, obese with abdominal fat deposition and had lower HDL values as well as higher triglycerides and glucose levels. Homeostasis model assessment-insulin resistant (HOMA-IR) test values in these women were compatible with insulin resistance (P < 0.05). CRP and HSP60 concentrations were higher in women with MetS than in women without MetS (P < 0.05). HSP60, anti-HSP70, and CRP concentrations increased with the number of features indicative of MetS (P < 0.05). There was a significant positive correlation between anti-HSP70 and WC, blood pressure and HOMA-IR, and between CRP and WC, blood pressure, glucose, HOMA-IR, and triglycerides (P < 0.05). In postmenopausal women, serum HSP60 and anti-HSP70 concentrations increased with accumulating features of the metabolic syndrome. These results suggest a greater immune activation that is associated with cardiovascular risk in postmenopausal women with metabolic syndrome.